When teachers compare argumentative texts: Decisions informed by multiple complex aspects of text quality - Lesterhuis, Marije (L1-Educational Studies in Language and Literature, 2018)
Insight into aspects that guide teachers' decisions when assessing student text quality is crucial to an understanding of the validity of text scores. Such research has been lacking in the context of comparative methods which are, however, increasingly being used for text assessment purposes. This study reports on the aspects of argumentative texts that guide Flemish teachers' decisions when using the comparative judgement method. In using this method, teachers indicate which text of a pair is of higher quality. 27 teachers explained 23 comparative judgements in a decision statement, when comparing randomly selected texts written by 135 students in their fifth year of general secondary education. This resulted in 596 statements referring to 2054 segments of aspects of text quality. Firstly, an inductive analysis revealed that teachers consider a wide range of aspects with regard to text quality when making comparison decisions. Secondly, the deductive aggregation of these aspects showed that most decisions are informed by the organisation and argumentation of the texts. Lastly, almost all statements reported complex aspects of text quality, whereas half of the decision statements also showed a reflection on the rule-applying aspects of text quality. We conclude that comparative judgement encourages teachers to make decisions on complex and multiple aspects of text quality. Further research should elaborate on whether the aspects that informed teachers' decisions are related to the text they choose, and whether teachers differ in the aspects to which they refer.